Gene Expression and Mutational Landscape in a PMEC Patient With Low to Intermediate-High Grade Transition - Dong, Weijie; Zhu, Bing; You, Yan; Wang, Bing; Fu, Dan; Wang, Daoxin; Li, He; Li, Changyi (Frontiers in Oncology, 2022)
Primary pulmonary mucoepidermoid carcinoma (PMEC) is the very rare form in the lung carcinomas. Due to the low incidence, little is known about its inherent genetic variation characteristics. The uniform treatment for PMEC has not been determined. In this case, we present a 45-year-old male with stage IA PMEC. The surgical specimens contained changes from low to intermedium-to-high grade. We performed integrative analysis of whole-exome sequencing (WES-seq) and messager ribonucleic acid sequencing (RNA-seq), to compare the molecular changes in the different lesions. Molecular testing exhibits the specimens harboring CRTC3-MAML2 fusion. The copy number gain of PDPK1 is only present in high-grade regional specimens. We also explore the level of immune infiltration by CIBERSORT. To our knowledge, this is the first report to describe a case of PMEC in the low to medium-high grade transition with multi-omics analysis.